Kepastian Hukum dalam Proses Integrasi Pasca Akuisisi: Studi terhadap Perlindungan Hak Pemegang Saham Berdasarkan UUPT dan POJK - Audrey Adyuta Putri; Elisatris Gultom (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze legal certainty in the post-acquisition integration process and its impact on the protection of shareholders' rights based on the Limited Liability Company Law (UUPT) and the Financial Services Authority Regulation (POJK). Using a normative legal approach and case studies, this study finds that the absence of specific regulations, weak supervisory mechanisms, and the lack of synchronization of corporate culture are the main factors causing integration failure and potential losses for shareholders, especially minority shareholders. To realize a fair and sustainable integration process, it is necessary to strengthen internal governance based on the principles of Good Corporate Governance (GCG), risk-based supervision, and external regulatory reforms that are more responsive to business dynamics. This study recommends the active involvement of authorities in regulating post-acquisition integration and the implementation of transparent and accountable evaluation mechanisms to protect the interests of all stakeholders. These findings contribute to the formulation of a fair and adaptive integration model in the Indonesian legal and economic environment.